Short-Term Safety and Efficacy of Onasemnogene Abeparvovec in 10 Patients with Spinal Muscular Atrophy: Cohort Study - Kristina S. Nevmerzhitskaya; Elena Yu. Sapego; Daria A. Morozova (Вопросы современной педиатрии, 2021)
Background. The efficacy and safety of onasemnogene abeparvovec have been demonstrated in patients with spinal muscular atrophy (SMA) in several clinical and observational studies. Gene replacement therapy results in Russian patients with SMA is not investigated yet.Objective. The aim of the study is to study the safety and efficacy of onasemnogene abeparvovec in children with SMA in real clinical practice.Methods. The study included patients with proximal 5q SMA administered with onasemnogene abeparvovec. Diagnosis was verified by biallelic deletion in the 7th exon of the SMN1 gene. Gene replacement therapy was administered according to the decision of neurologists consensus in case of the absence of antibodies to the adeno-associated serotype 9 virus. The therapy safety was estimated via clinical and laboratory data from the hospital (at least 7 days) and from outpatient departments (at least 60 days). Efficacy was estimated via CHOP INTEND scale and mastering new motor skills ≥ 6 months after therapy onset.Results. Treatment outcomes were studied in 10 SMA patients aged 19 months (15; 21). All patients developed at least one clinical manifestation (hyperthermia, vomiting, lethargy and/or loose stool) associated with drug administration during the first week of follow-up. Increased hepatic transaminases activity and monocytosis was recorded in all patients, thrombocytopenia — in 9, neutropenia — in 5, increased troponin I concentration — in 3. In three cases it was necessary to increase the oral prednisolone dose of to 2 mg/kg, in one case — the dexamethasone pulse therapy dose. The therapy efficacy was monitored ≥ 6 months after therapy onset via the CHOP INTEND scale in 2 patients (scores increased by 32 and 19 points, respectively), and via mastering new motor skills in 8 patients (positive dynamics was noted in 7 cases).Conclusion. The onasemnogene abeparvovec is relatively safe and quite effective for using in real clinical practice